The Role of Community Participation in Managing Village Fund Allocations: Corrupt Prevention Case Study - Musyafir, Ashar; Syukur, Muhammad; Ahmad, Ridwan Said (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2024)
Management of village fund allocation is a government program to meet village needs as capital to improve village development. However, in reality, the routine allocation of village funds provided by the Central Government to villages is prone to corruption. This research aims to describe and explain the urgency of the need to increase community participation in preventing corruption to improve the quality of development and public services in villages. Next, describe and analyze the process of managing village fund allocation. The research method used is qualitative-descriptive research with literature study. The results of this research show the urgency of efforts that can be made to increase public participation in preventing corruption, namely by providing adequate access to information on village programs and budgets, community awareness to participate, easy access to communication with village officials by the community, optimal village community organizations, and optimization role of BPD. Furthermore, planning in managing village fund allocations involves or involves the community in determining planning, the implementation of ADD management has gone well, this can be seen from the use of ADD received in accordance with applicable regulations. However, achieving the goal of providing ADD as stated in the Village Law has not been carried out optimally and guidance on ADD management, especially in terms of administration of ADD management, has been carried out well thanks to support from the village government to always learn about bookkeeping management and completeness of activity reporting.